Investigation of Mechanical Thrombectomy in Elderly Patients over 85 Years Old: A Multicenter Study - Kohei SHIBUYA; Hitoshi HASEGAWA; Tomoaki SUZUKI; Haruhiko TAKAHASHI; Kei NISHIYAMA; Makoto OISHI; Yukihiko FUJII (Neurologia Medico-Chirurgica, 2023)
In Japan, which has a super-aging society, there are increasing opportunities to perform mechanical thrombectomy for the elderly; however, there is no recorded evidence of thrombectomy for the elderly. This study examined the usefulness of thrombectomy in the elderly. We retrospectively analyzed patient data using a multicenter acute ischemic stroke registry (NGT-FAST). We examined outcomes in patients 75 years and older who underwent thrombectomies between January 1, 2021, and December 31, 2021. The patients were divided into two groups: the 75-84-year-old group and the 85+-year-old group. There was no difference in the pretreatment National Institutes of Health Stroke Scale score or Alberta Stroke Program Early Computed Tomography Score between the two groups, but the 85+-year-old group had a significantly lower rate of pre-stroke modified Rankin Scale (mRS) score of 0-2. There were no differences in time from onset to treatment or effective recanalization rate, but complications tended to be more common in the 85+-year-old group. The number of patients with a good outcome at discharge (an mRS score of 0-3) was significantly lower in the 85+-year-old group than in the 75-84-year-old group. In addition, 90.9% of patients in the 85+-year-old group with a pre-stroke mRS score of 3 deteriorated after treatment. The pre-stroke mRS score is very important in determining the indication for thrombectomy in the elderly because their preoperative condition is more likely to influence the outcome than that of younger patients.